Facultad de odontología: para la salud 65 años de educación. La investigación en la historia de la Facultad. Artículo especial - Franco, Ángela María; Isaza, Diana María; Arismendi, Jorge Alberto (Revista Facultad de Odontología Universidad de Antioquia, 2009)
As we celebrate 65 years of our School’s foundation at the University of Antioquia, this essay collects the facts that make the precedents of the scientific activity in our School, as well as the most significant ones at the present time and, some research projects that are important for the future. This recollection doe not have the rigor of a historic review, it only pretends to be an homage to the many persons that in a persistent and sometimes anonymous way contributed to plant the seeds of a job of which there is still a lot to be done.